Effect of incorporating Lode angle parameter into a fracture criterion in predicting ballistic impact behavior of double-layered 2024-T351 aluminum alloy plates against blunt projectiles. (February 2022) - Xiao, Xinke; Shi, Yahui; Wang, Yaopei; Chen, Xiaozhen; Jia, Bin
HIGHLIGHTS: Monolithic plates fail by shear plugging without global bending. For double-layered configurations, the first plate fails by shear plugging and the second plate fails by tensile stretching and global bending. By replacing monolithic plates with double-layered ones, the ballistic resistance improves. Within the stress state of ballistic impact tests, the ductility of AA2024-T351 is sensitive to Lode angle parameter. Lode dependent MMC criterion gives more accurate predictions than Lode independent JC criterion. Abstract: Recent studies showed that the ductility of some metals was affected by not only stress triaxiality but also Lode angle parameter. However, the majority of impact-related simulations used Lode independent fracture criteria. The necessity of incorporating Lode angle parameter into a fracture criterion in predicting ballistic impact behavior of monolithic 2024-T351 aluminum alloy (AA2024-T351) plates has been previously addressed in the work of Xiao et al. [1] . This paper serves as an extension by considering plates with double-layered configuration and the same total thickness. Ballistic impact tests were performed on 4.82 + 4.82 mm thick double-layered plates. Blunt projectiles with dimensions of Φ 12.66×50.56 mm 3 and a nominal mass of 50 g were used, and the impact velocities ranged from 133.4 to 363.8 m/s. According to the experimentally obtained data, ballistic limit velocities (BLVs) were calculated and fracture patterns of post-test plates were analyzed. It was found that for double-layered configurations, the first plate failed by shear plugging and the second plate failed by tensile stretching and global deformation. By replacing monolithic plates with double-layered ones, the BLV increased from 138.4 to 180.1 m/s, a 30% improvement in ballistic resistance. Subsequently, numerical simulations of ballistic impact tests were performed by software ABAQUS/Explicit. Mechanical property of AA2024-T351 was described by Johnson-Cook (JC) plasticity model accompanied with either the Lode independent JC fracture criterion or the Lode dependent modified Mohr-Coulomb (MMC) fracture criterion. The numerical results were compared with those obtained from experiments. It was found that MMC criterion predicted BLVs more accurately than JC criterion. The prediction errors for MMC and JC criteria were respectively 3.3% and 11.4%, with the former being merely one-third of the latter. The overall failure modes of double-layered plates were correctly predicted by both JC and MMC fracture criteria. However, details of the fracture patterns, such as the formation of fragments, the shape and number of ejected plugs, and the initiation and propagation of cracks, were better captured by MMC criterion than by JC criterion. Detailed analysis shows that the stress state governing ballistic impact tests locates in the range where Lode angle parameter is strong enough to induce a significant difference between JC and MMC criteria. Under such stress state, the ductility of AA2024-T351 is correctly predicted by the Lode dependent MMC criterion but is overestimated by the Lode independent JC criterion. Graphical abstract: Image, graphical abstract